(untitled) (The Pakistan Development Review, 2020)
This theoretical paper looks into joint determination of corruption and development where there is a decentralised bureaucratic setup in a multi-tiered system: tier one bureaucrats and tier two bureaucrats. Corruption takes place at two levels, firstly when tier one bureaucrats collude with households for tax evasion, and secondly when tier one and tier two bureaucrats collude to hide corruption. This paper determines that at high levels of corruption, there is low development, and at a low incidence of corruption, there is high development. This paper postulates that for a developing country like Pakistan, low tax collection due to poor institutional decentralisation leads to low economic growth and development. JEL Classifications: E02, E26, E42 Keywords: Corruption, Tax Evasion, Economic Growth